2013
DOI: 10.7860/jcdr/2013/6550.3339
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar Gas Exchange and Pulmonary Functions in Patients with Type II Diabetes Mellitus

Abstract: We conclude that the pulmonary function parameters like FVC, FEV1, PEFR, PIF, FIVC, TLC and alveolar gas exchange were significantly reduced in patients with type II diabetes. The patients with Type II diabetes mellitus had a restrictive pattern of respiratory abnormality. The patients with poor glycaemic control( HbA1c > 7) had reduced alveolar diffusion which was not dependent on the duration of diabetes. The impaired respiratory function may give way for the development of pulmonary complications. Spirometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 20 publications
2
8
0
Order By: Relevance
“…Recently, a prospective study including 7524 participants also reported that diabetes is not associated with obstructive pulmonary function impairment [ 6 ]. In addition, some studies with small sample size reported that not only DLCOc%pred but also DLCOc/VA%pred was decreased in T2DM [ 23 , 24 ]. However, in current study, there was no statistically difference in DLCOc/VA%pred, which may be associated with a decrease in alveolar ventilation (VA) induced by restrictive ventilation dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a prospective study including 7524 participants also reported that diabetes is not associated with obstructive pulmonary function impairment [ 6 ]. In addition, some studies with small sample size reported that not only DLCOc%pred but also DLCOc/VA%pred was decreased in T2DM [ 23 , 24 ]. However, in current study, there was no statistically difference in DLCOc/VA%pred, which may be associated with a decrease in alveolar ventilation (VA) induced by restrictive ventilation dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that dysglycemia affects lung connective tissue metabolism leading to thickening of the alveolar epithelial and endothelial basement membrane [ 18 21 ]. Furthermore, pulmonary microangiography is a characteristic manifestation of diabetes [ 22 , 23 ]. Such findings results in reduced alveolar gas exchange in patients with type 1 and 2 DM.…”
Section: Discussionmentioning
confidence: 99%
“…BGB–alveolar gas exchange defects are present in diabetic patients and may be linked to rapid progression of COVID-19 requiring assisted ventilation as well as increased morbidity and mortality ( Figures 1 , 2 ). 4 7 …”
Section: Introductionmentioning
confidence: 99%